(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article examines the correlation between psychological stress and managerial qualities in department heads of higher education institutions. The study shows that increased stress can hinder effective leadership, while emotional stability and resilience support the development of strong managerial competencies.